Clinical impact of KMT2C and SPRY4 expression levels in intensively treated younger adult acute myeloid leukemia patients - Kayser, Sabine; Benner, Axel; Müller-Tidow, Carsten; Ho, Anthony Dick; Schlenk, Richard Friedrich; Krämer, Alwin (European journal of haematology, 2017)
Objective To evaluate the prognostic impact of gene expression levels (ELs) of two tumor suppressor genes, sprouty 4 (SPRY4, located on 5q) and lysine methyltransferase 2C (KMT2C, located on 7q) in correlation with clinical characteristics and genetic abnormalities assessed at initial diagnosis in acute myeloid leukemia (AML). Method Gene expression levels were measured on cDNA by RT-qPCR from diagnostic bone marrow samples of 275 intensively treated adult AML patients (median age, 48 years). Results KMT2C ELs were significantly lower in abn7q/-7 (P = .001), whereas SPRY4 ELs were not associated with abn5q/-5. Higher KMT2C and SPRY4 ELs were significantly associated with lower genetic risk groups as defined by the European LeukemiaNet classification. Additionally, KMT2C ELs were lower in cytogenetically normal patients with DNMT3A (P = .01) or FLT3-ITD mutations (P = .05). KMT2C ELs were not associated with prognosis, whereas higher SPRY4 ELs showed a favorable impact on event-free (EFS, P = .01), relapse-free (RFS, P = .01) and in-trend on overall survival (P = .06) for cytogenetically abnormal patients, which was confirmed in multivariable analysis for EFS (HR, 0.84; 95%-CI, 0.73-0.97; P = .02) and RFS (HR, 0.85; 95%-CI, 0.73-0.98; P = .02). Conclusion Our data indicate that KMT2C ELs are associated with specific genetic features and that SPRY4 ELs may add prognostic information.